2012
DOI: 10.3109/10428194.2011.626883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parathyroid hormone-related protein and macrophage inflammatory protein-1α in Jurkat T-cells on tumor formationin vivoand expression of apoptosis regulatory genesin vitro

Abstract: Parathyroid hormone-related protein (PTHrP) and macrophage inflammatory protein-1α (MIP-1α) have been implicated in the pathogenesis of adult T-cell leukemia/lymphoma, but their effects on T-cells have not been well studied. Here we analyzed the functions of PTHrP and MIP-1α on T-cell growth and death both in vitro and in vivo by overexpressing either factor in human Jurkat T-cells. PTHrP or MIP-1α did not affect Jurkat cell growth in vitro, but PTHrP increased their sensitivity to apoptosis. Importantly, PTHr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 85 publications
(97 reference statements)
0
8
0
Order By: Relevance
“…A major contributor to this co-operation is tumor production of PTHrP, together with the several other cancer-derived factors that influence bone metastasis establishment, including prostaglandins and cytokines (96) and of factors favoring the homing and/or adherence of cancer cells to bone (99). Although this emphasizes PTHrP involvement in breast cancer, increasing evidence implicates it in prostate, lung, renal, colon, lymphoid and other cancers (100104). …”
Section: Pthrp and Cancermentioning
confidence: 99%
“…A major contributor to this co-operation is tumor production of PTHrP, together with the several other cancer-derived factors that influence bone metastasis establishment, including prostaglandins and cytokines (96) and of factors favoring the homing and/or adherence of cancer cells to bone (99). Although this emphasizes PTHrP involvement in breast cancer, increasing evidence implicates it in prostate, lung, renal, colon, lymphoid and other cancers (100104). …”
Section: Pthrp and Cancermentioning
confidence: 99%
“…Decision tree analysis revealed genes CD40LG and GBP2 as discriminators of ATLL and HAM/TSP, offering accuracy rates of 100% and 84.2%, respectively. A previous report identified lower CD40LG expression in cells expressing PTHrP and MIP-1α, two proteins associated with ATLL progression (Shu et al, 2012). The second marker identified herein, GBP2 , was previously associated with tax protein activity in HTLV-1 (Arainga et al, 2012).…”
Section: Discussionmentioning
confidence: 87%
“…Human T cell leukemia Jurkat cell line with stable transfection of PTHrP, MIP-1α, or pcDNA3.1 vector and luciferase expression were previously generated and characterized [24]. These three cell lines Jurkat-pcDNA-luc, Jurkat-PTHrP-luc, and Jurkat-MIP-1α-luc will be referred to as Jurkat-pcDNA, Jurkat-PTHrP, or Jurkat-MIP-1α throughout this paper.…”
Section: Cell Linesmentioning
confidence: 99%
“…Real-time RT-PCR (qRT-PCR) was used to confirm expression levels of PTHrP and MIP-1α mRNA for this study (not shown; see ref. [24] for original figure). Secretion of PTHrP in Jurkat-PTHrP cells was confirmed by immunoassay at the Diagnostic Center for Population and Animal Health at Michigan State University {Jurkat-PTHrP (42.4 pmol/l)}.…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation